2021
DOI: 10.1007/s11033-021-06860-6
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional analysis of CCT family genes in pigeonpea

Abstract: Pigeonpea (Cajanus cajan (L) Millsp) is a short-day plant in which the owering is highly sensitive to photoperiod. A better understanding of the genes modulating photoresponse and owering time is critical to developing photoperiod insensitive pigeonpea cultivars for cultivation across the seasons. We identi ed 33 CCT family genes (CcCCT1-CcCCT33) in C. cajan and localized them on 10 chromosomes and nine genomic scaffolds. The structural analysis of CCT family genes revealed a considerable variation in length a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A total of 26 BrCMF genes were identified based on comparison of homologous genes of the known AtCMF family with those in the B. rapa genome database. A gene member without the CCT domain was identified and omitted, which yielded a total of 25 predicted CMF genes, exceeding the number of CMF genes reported in Oryza sativa (19) [ 7 ], Oryza rufipogon (19) [ 9 ], Zea mays (14) [ 13 ], Setaria italica (19) [ 11 ], Aegilops tauschii (12) [ 14 ], Medicago truncatula (18) [ 10 ], Glycine max (19) [ 12 ], Cajanus cajan L. (12) [ 15 ], and Populus trichocarpa (14) [ 16 ]. These genes were named according to their chromosomal distribution.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of 26 BrCMF genes were identified based on comparison of homologous genes of the known AtCMF family with those in the B. rapa genome database. A gene member without the CCT domain was identified and omitted, which yielded a total of 25 predicted CMF genes, exceeding the number of CMF genes reported in Oryza sativa (19) [ 7 ], Oryza rufipogon (19) [ 9 ], Zea mays (14) [ 13 ], Setaria italica (19) [ 11 ], Aegilops tauschii (12) [ 14 ], Medicago truncatula (18) [ 10 ], Glycine max (19) [ 12 ], Cajanus cajan L. (12) [ 15 ], and Populus trichocarpa (14) [ 16 ]. These genes were named according to their chromosomal distribution.…”
Section: Resultsmentioning
confidence: 99%
“…Medicago truncatula (18) [10], Glycine max (19) [12], Cajanus cajan L. (12) [15], and Populus trichocarpa (14) [16]. These genes were named according to their chromosomal distribution.…”
Section: Identification and Analysis Of Brcmfsmentioning
confidence: 99%
See 1 more Smart Citation
“…With this, homozygous genotypes to this trait could be achieved rapidly. Also, because a low frequency of plants that flower is expected (Tribhuvan et al, 2022; this study), the space and labor should not be a problem to carry out progeny tests. The bulk method should be used in later generations (F 5 -F 7 ) to select photoperiod-insensitive genotypes that have a higher agronomic performance and commercial seed size and color, especially if labor and space conditions are limited.…”
Section: 2mentioning
confidence: 94%
“…The genetics for the indeterminate flowering habit and photoperiod sensitivity have been reported to be inherited by one or multiple dominant genes (Kapoor & Gupta, 1991;Mir et al, 2014;Saxena et al, 2021a). The CcTFL1 locus, located on chromosome 3, was reported as the candidate gene for flowering habit (Mendapara et al, 2023;Mir et al, 2014;Saxena et al, 2017), while the CCT family of genes mostly observed on chromosomes 3, 7, and 11 was reported to be responsible for photoperiod sensitivity in pigeonpea (Tribhuvan et al, 2022). Readers interested in a detailed explanation of the position and expression of these genes can refer to Bhattacharjee et al (2023), Mendapara et al (2023), Saxena et al (2017), and Tribhuvan et al (2020.…”
Section: Introductionmentioning
confidence: 99%